TINJAUAN YURIDIS TENTANG PENYELESAIAN SENGKETA MASYARAKAT DALAM PENENTUAN PEMERINTAHAN DI DISTRIK SELEMKAIKABUPATEN TAMBRAUW PAPUA BARAT DAYA - Gifelem, Nelwan; M. Syauta, Novalin; Baho, Dayen (Ensiklopedia of Journal, 2024)
Disputes arise due to differences in interests between one legal subject and another legal subject that the Tambrauw Regency Government area, namely up to Selemkai District, this results in disputes. The purpose of this writing is to find out what causes community disputes in Selemkai District between Sorong Regency and Tambaruw Regency, to find out what causes community disputes in determining the Government in Selemkai District, Tambrauw Regency and how to resolve community disputes in determining the Government in Selemkai District, Tambrauw Regency.The research method used is normative empirical, the types and sources of data used are primary data and secondary data. The data collection techniques used are literature studies, interviews and observations, and the data analysis technique is descriptive qualitative.The results of the study obtained are the cause of the community dispute in Selemkai District in determining the government between Sorong Regency and Tambrauw Regency, due to Law Number 14 of 2013 concerning the Establishment of Tambrauw Regency and Regional Regulation Number 4 of 2017 concerning the Arrangement of District Boundaries, where Selemkai District is included in the Tambrauw Regency Government area, this is not approved by some of the Selemkai District community because initially Selemkai District which was a division of Moraid District was included in the Sorong Regency government area and the boundaries of customary areas, tribes, languages and customs of the community in Tambrauw Regency are different from the community in Selemkai District, where the community in Selemkai District is part of the Moi tribe indigenous community. In addition, the reason is that some of the people in Selemkai District work for the Sorong Regency government so the]y refuse to be part of Tambrauw Regency and the resolution of community disputes in determining the government in Selemkai District is carried out through mediation outside the court/non-litigation. mediation conducted outside the courts in Selemkai District, namely by conducting legal counseling to the community in Selemkai District, which was conducted by the Sorong Regency Police, provided many benefits for both parties. The results of the mediation conducted by the Sorong Regency Police did not reach a meeting point because the Selemkai District community remained with its founder, so the Sorong Police took a middle ground by directing the community that the Selemkai District government located in Sorong Regency and Tambrauw Regency may run its government simultaneously without disturbing the other government areas. This result is what makes the boundary government of the two parties continue to run until now.Keywords: Community Dispute, Government Dispute